Using Semistructured Surveys to Improve Citizen Science Data for Monitoring Biodiversity. (18th March 2019) - Kelling, Steve; Johnston, Alison; Bonn, Aletta; Fink, Daniel; Ruiz-Gutierrez, Viviana; Bonney, Rick; Fernandez, Miguel; Hochachka, Wesley M; Julliard, Romain; Kraemer, Roland; Guralnick, Robert
Abstract: Biodiversity is being lost at an unprecedented rate, and monitoring is crucial for understanding the causal drivers and assessing solutions. Most biodiversity monitoring data are collected by volunteers through citizen science projects, and often crucial information is lacking to account for the inevitable biases that observers introduce during data collection. We contend that citizen science projects intended to support biodiversity monitoring must gather information about the observation process as well as species occurrence. We illustrate this using eBird, a global citizen science project that collects information on bird occurrences as well as vital contextual information on the observation process while maintaining broad participation. Our fundamental argument is that regardless of what species are being monitored, when citizen science projects collect a small set of basic information about how participants make their observations, the scientific value of the data collected will be dramatically improved.